“He Speaks Two Languages at the Same Time … So, Why Should It Be Sad?”—Dutch Multilingual Children’s Beliefs About Language Use and Language Mixing In- and Outside the Home - Eva Knopp; Sterre Turling; Chantal van Dijk; Claire Goriot (Languages)
This study investigates the beliefs about multilingualism and the multilingual language use of multilingual children living in the Netherlands, a highly diverse and multilingual society. We interviewed 26 8- to 12-year-old primary school children with different home languages (i.e., English, German, Polish or Turkish). Children indicated how a multilingual alter-ego felt about multilingual language use scenarios and why. The scenarios comprised situations using their different languages with parents, friends or teachers in monolingual and multilingual modes. Children overwhelmingly associated neutral or positive feelings with using the societal and home language. These feelings were not consistently affected by the societal prestige of their home language (measured by English and German vs. Polish and Turkish as their home language). The content analysis indicated that, besides competence, accommodating the interlocutor, personal preference and normality were the most frequent explanations children provided for their emotional reactions. Our findings indicate that the participating children experience being multilingual as normal and are not (yet) negatively affected in their attitudes despite their experience with a monolingual bias at school. Although no effects of home language prestige emerged, differences between children from specific home language communities suggest that myths about multilingual competence and code-mixing persist.